Language-Model-Based Parsing and English Generation for Unscoped Episodic Logical Forms - Erin Gibson; Lane Lawley (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Unscoped Episodic Logical Forms (ULF) is a semantic representation for English sentences which captures semantic type structure, allows for linguistic inferences, and provides a basis for further resolution into Episodic Logic (EL). We present an application of pre-trained autoregressive language models to the task of rendering ULFs into English, and show that ULF's properties reduce the required training data volume for this approach when compared to AMR. We also show that the same system, when applied in reverse, performs well as an English-to-ULF parser.